Unravelling the population dynamics of the Mediterranean bryozoan Pentapora fascialis to assess its role as an indicator of recreational diving for adaptive management of marine protected areas. (February 2020) - Pagès-Escolà, Marta; Hereu, Bernat; Rovira, Graciel·la; Medrano, Alba; Aspillaga, Eneko; Capdevila, Pol; Linares, Cristina
Highlights: Diving impacts on the density, recruitment, survival, and size of the colonies. Bryozoan recruitment events are stochastic showing inter-annual variation. Higher growth and lower necrosis rates were found during the colder months. Bryozoan densities on non-frequented locations have increased since the 1990s. Pentapora fascialis showed a fast population dynamics with high capacity of recovery. Abstract: Marine Protected Areas (MPAs) have been recognized as effective management and conservation tools to protect marine coastal ecosystems. However, due to an increasing interest in marine ecosystems, recreational activities such as scuba diving are rapidly growing in these areas, highlighting the need to implement adaptive management strategies based on continuous monitoring and evaluation of protected areas. To date, several studies have quantified the impact of diving using benthic species as indicators, such as bryozoans, but usually ignoring their population dynamics. Here, we studied the population dynamics of the abundant and common bryozoan Pentapora fascialis on a Mediterranean MPA with high levels of diving activity. Specifically, we monitored eight different localities with two different levels of diving frequentation (non-frequented versus frequented) from October 2015 to October 2018, accounting for the demographic parameters before and after the summer. Our results showed the impact of diving on the density, recruitment, survival, and size of colonies, reaching higher values on non-frequented localities. In addition, we detected two peaks of recruitment during July 2016 and July 2018, suggesting that bryozoan recruitment events are stochastic, with a high inter-annual variation. Contrastingly, regardless of the diver frequentation level, we found higher growth rates during the colder months and higher necrosis rates after the summer in all the studied localities. Besides the aforementioned differences, the densities observed in this study were much higher compared to previous studies performed in the same area during the 1990s. Taken together, these results suggested rapid population dynamics of P. fascialis, with fast growth rates and a high capacity to recover from perturbations. Despite the quantified effects of diving on our studied species, their abundance in frequented sites remained very low over the whole study period, compromising the use of P. fascialis as an optimal indicator of diving impact for adaptive management of temperate benthic populations. Overall, our results highlight the importance of continuous monitoring programs to unravel the population dynamics of indicator species to effectively manage marine populations and evaluate the impact of human activities on marine protected areas.